Dramaturgy of Discourse: Cognitive-Pragmatic Potential of Metamarker ‘V TAKOM TONE’ [in such a tone] - N. N. Beloshitskaya (Научный диалог, 2024)
The phenomenon of discursive dramaturgy is interpreted in the article as the planning and construction of an effective communicative strategy by the linguistic persona in specific socio-cultural conditions. The methodological basis for this study is provided by the concepts of A. V. Olyanich, I. Hoffman, J. Habermas, and V. I. Karasik. The phrase ‘v takom tone’ [in such a tone] is examined as a pragmatic metamarker of discursive dramaturgy tactics. The research material consists of textual excerpts from literary works in the National Corpus of the Russian. 74 excerpts describing communicative situations representing genres of conflict or potentially conflictual interactions were selected. In 26 of them, the metamarker ‘v takom tone’ [in such a tone] was used to model situations related to genres of personality-oriented discourse. In 16 excerpts, this metamarker models situations related to genres of status-oriented discourse. In 32 excerpts, the phrase was used as a cognitive plan metamarker. The results of the study allow us to conclude about the frequency of marking with the phrase ‘v takom tone’ [in such a tone] of social roles, tactics of maintaining social face, “sincere misunderstanding,” threat, and conflict avoidance. The metamarker ‘v takom tone’ [in such a tone] helps the interaction addressee to explicitize the addressee’s cognitive plan — to identify intentions and desires, predict a change in tactics.